2023
DOI: 10.1002/anie.202219053
|View full text |Cite
|
Sign up to set email alerts
|

Pore Aperture Control Toward Size‐Exclusion‐Based Hydrocarbon Separations

Abstract: Metal-organic frameworks (MOFs) have been proposed as a promising material for non-thermal chemical separations owing to their high structural diversity and tunability. Here, we report the synthesis of a zinc-based MOF containing a three-dimensional (3D) linker, bicyclo[2.2.2]octane-1,4-dicarboxylic acid, with high thermal stability towards the separation of hexane isomers. The incorporation of the 3D linker enhances the structural stability and provides well-defined pore apertures/channels with sub-Ångstrom p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…These changes can significantly impact the performance of separations that aim to distinguish between molecules with sub-angstrom differences in size through being able to conform to the guest molecule by rotating the 2D linker. To address this issue, previous research has shown that the incorporation of three-dimensional (3D) linkers based on icosahedral carboranes or polycyclic compounds can lead to structures that are analogous to those with 2D benzene-based linkers. Consequently, the pores in the former structures are smaller due to the increased dimensionality of the linkers. This feature can be useful when separating molecules with sub-angstrom differences in size because using 3D linkers can minimize variations in pore size caused by variable linker orientations, leading to enhanced control over the separation.…”
Section: Introductionmentioning
confidence: 99%
“…These changes can significantly impact the performance of separations that aim to distinguish between molecules with sub-angstrom differences in size through being able to conform to the guest molecule by rotating the 2D linker. To address this issue, previous research has shown that the incorporation of three-dimensional (3D) linkers based on icosahedral carboranes or polycyclic compounds can lead to structures that are analogous to those with 2D benzene-based linkers. Consequently, the pores in the former structures are smaller due to the increased dimensionality of the linkers. This feature can be useful when separating molecules with sub-angstrom differences in size because using 3D linkers can minimize variations in pore size caused by variable linker orientations, leading to enhanced control over the separation.…”
Section: Introductionmentioning
confidence: 99%
“…In the second study from Farha and co‐workers, a zinc‐based MOF was synthesized containing 1,4‐bicyclo[2.2.2]octanedicarboxylate (bodc), ([Zn(bodc)] (NU‐2200, 9 ), which demonstrated impressive thermal stability and high separation selectivity toward hexane isomers (Figure 7b,e–f). [60] This MOF demonstrated sieving and thermodynamic differentiation of hexane isomers based on single‐component adsorption isotherms which was further corroborated using multicomponent batch liquid uptake experiments.…”
Section: Separation and Adsorption Investigationsmentioning
confidence: 55%
“…In the second study from Farha and co-workers, a zincbased MOF was synthesized containing 1,4-bicyclo-[2.2.2]octanedicarboxylate (bodc), ([Zn(bodc)] (NU-2200, 9), which demonstrated impressive thermal stability and high separation selectivity toward hexane isomers (Figure 7b,e-f). [60] This MOF demonstrated sieving and thermodynamic differentiation of hexane isomers based on single-…”
Section: Hexane Isomer Separationsmentioning
confidence: 99%